More than 1 million people reached with improved Participatory Scenario Planning processes in Kenya - Grossi, Amanda; Ghosh, Aniruddha (2025)
Through facilitation of multistakeholder dialogues, coordination frameworks, and investment mobilization by AICCRA, more than 328,000 community stakeholders across nine Kenyan counties were directly reached with improved and streamlined climate information services to inform seasonal planning, with an estimated 1,000,600 reached indirectly. The climate-information services were delivered through Participatory Scenario Planning (PSP) processes, newly harmonized amongst more than 10 PSP implementers from public and private sectors who adopted action plans for coordinated finance, sustainability, quality, and timeliness of these processes.